Pengembangan SPS Inaportnet dengan Integrasi Sistem Informasi Perwira Jaga Berbasis Web di Pelabuhan Tanjung Perak Surabaya - Firmansyah, Ryzki Arif; Wani Sihaloho, Otri; Asdiana, Femmy; Amrullah, Romanda Annas; Arisusanty, Dian Junita; I.P. Turnip, Guntur (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
In the era of rapid digitalization, technology allows fast access to information via the internet. Digitalization of information systems is important to increase organizational efficiency. In the port sector, the Harbormaster's Office and the Tanjung Perak Surabaya First Class Port Authority have used Inaportnet to support shipping activities. One of the main services is the Sailing Approval Letter (SPB) which has been digitized in the Inaportnet SPS system. However, information dissemination by duty officers is still limited to WhatsApp groups and personal communications, causing inefficiencies. This research aims to evaluate the development and integration of an online guard officer information system using PHP. This research was carried out using the research and development method using a prototype model. Testing was carried out using the black box method with results showing a 100% functionality success rate. This integration produces additional features such as the main page, guard officer information dashboard, admin login and logout menus, as well as information notifications that can be used on all platforms. The research results show that this system increases operational effectiveness and efficiency at the Harbor Master of Tanjung Perak Surabaya. It is hoped that these findings can become a reference for the development of information systems in the maritime sector and increase understanding in data management.